Effect of Accelerated Aging on the Color Stability of Light-cured Res-in Cement and Flowable Composite Through Porcelain Laminate Veneer - Maryam Hoorizad Ganjkar; Haleh Heshmat; Mahdis Gholamisinaki; Mansooreh Emami Arjomand (Journal of Islamic Dental Association of Iran, 2017)
Background and Aim: Changing the color of resin luting cements could affect the aesthetic appearance of thin porcelain veneer. The aim of this in vitro study was to evaluate the effect of artificially accelerated aging on color stability of light-cured resin cement and flowable composite as a luting agent through the porcelain veneer. Materials and Methods: This experimental study was carried out on 4 groups each contained 5 specimens with the dimension of 8 mm in diameter and 1 mm thickness. In group 1 and 2 five disks of resin cements and flowable composite were prepared, respectively. In group 3 and 4, the luting agent (1mm thickness) were bonded to feldspathic ceramic discs (1mm thickness). The color parameters of the samples in CIE Lab system were measured by spectrophotometer before and after artificially accelerat-ed aging. The results were statistically analyzed by Two-way ANOVA and t-test. Results: The highest color change was observed in Z350 flowable composite that showed a statistically significant difference with other groups (P<0.001). Differences between veneered groups were not significant (P=0.04). Color changes in groups 3 and 4 which covered with porcelain laminate were statistically lower than uncovered groups and the differences were significant (P<0.001). Conclusion: Accelerated aging process could influence clinically unacceptable changes in the color of luting agents (E3.3). However, porcelain laminate with 1 mm thickness could cover the color changes of luting agent.